Estabilización de suelos expansivos con ceniza de mazorca de maíz en la ciudad del Cusco - Quispe Vilca, Dante (2022)
Quarrying to improve road soils has been increasing over the years. This problem generates those ecosystems are depleted both in hills and in rivers. In this sense, the development of this study seeks to analyze the physical and chemical behavior of expansive soils with corn cob ash, which is an abundant and usually discarded product in the city of Cusco. The project is divided into three stages: in the first stage, a literature review was carried out on expansive soils and their improvement through chemical stabilization with different products. In the second stage, soil mechanics tests were carried out on the study soil without ash and with different amounts of corn cob ash. Finally, in the third stage, the results were analyzed using graphs and the optimal proportion was found to improve this type of soils with corn cob ash. Among the main improvements of the soil, it is possible to mention the reduction of plasticity by 42% for an ash percentage of 10%. Likewise, the bearing capacity of the CBR soil was also improved by 62% for an ash percentage of 8%. Therefore, it can be concluded that an expansive soil, usually replaced by granular quarry soils, can be improved with the addition of corn cob ash without damaging the ecosystems in the river beds and hills.